2010
DOI: 10.1345/aph.1m251
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib: An Oral Multitargeted Tyrosine Kinase Inhibitor for Use in Renal Cell Carcinoma

Abstract: Current data suggest pazopanib to be a viable treatment option as first-line therapy for advanced RCC. Data are awaited comparing pazopanib to other TKIs. Until results of head-to-head trials conducted of the various agents are available, it cannot be said whether pazopanib is more tolerable or efficacious than currently available therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…A review of the literature [46] identified thyroid dysfunction attributable to pazopanib with an incidence of 7% in patients treated for mRCC. The incidence and severity of thyroid dysfunction were explored in 578 pazopanib-treated patients participating in 3 trials, and it was found that 37 patients (6%) had elevated TSH at baseline (>5 mU/L), 167 (29%) had a TSH value of >5 mU/L during treatment.…”
Section: Pazopanibmentioning
confidence: 99%
“…A review of the literature [46] identified thyroid dysfunction attributable to pazopanib with an incidence of 7% in patients treated for mRCC. The incidence and severity of thyroid dysfunction were explored in 578 pazopanib-treated patients participating in 3 trials, and it was found that 37 patients (6%) had elevated TSH at baseline (>5 mU/L), 167 (29%) had a TSH value of >5 mU/L during treatment.…”
Section: Pazopanibmentioning
confidence: 99%
“…Patients treated with sunitinib have a twofold increased risk of requiring thyroid hormone replacement therapy compared with sorafenib. Hypothyroidism was not listed as a common AE in phase III studies of sorafenib or pazopanib (Escudier et al 2007a, 2009, Sternberg et al 2010; however, a randomized, double-blinded, placebocontrolled phase III study (La Plant & Louzon 2010) identified thyroid dysfunction attributable to pazopanib with an incidence of fewer than 10% (%7%) in patients treated for mRCC, with grade 3/4 events reported in !1% of patients (Sternberg et al 2010). These results have been confirmed by another randomized, open-label, phase III trial of pazopanib vs sunitinib (Motzer et al 2012) where hypothyroidism occurred among 12% of patients treated with pazopanib (Table 3; Motzer et al 2012).…”
Section: Sorafenib and Pazopanibmentioning
confidence: 99%
“…The newer agent, axitinib, is a potent, selective, second-generation inhibitor of VEGFR-1, 2, and 3 , Cohen et al 2008, Schiller et al 2009, Torino et al 2009, La Plant & Louzon 2010, Rugo et al 2011. A recent pivotal phase III trial randomized a total of 723 patients with advanced RCC in order to compare axitinib and sorafenib as second-line therapy (Table 1; Rini et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that tyrosine kinase inhibitors lead to thyroid dysfunction in various extent 20,21 , however its mechanism is still not clearly understood. 22 In this study, 8 out of 55 patients (14.5%) were diagnosed with thyroid dysfunction related to TKIs and TSH levels were at normal range after an initiation of levothyroxine treatment.…”
Section: Discussionmentioning
confidence: 99%